Consistency of Balinese Family Education in Forming a Love of Culture From an Early Childhood - Wati, Tita Pertama; Naimah, Naimah; Karimullah, Suud Sarim; Anggita, Indah Sri (Green Publisher Indonesia, 2022)
Forming cultural love is essential to stimulate a passion for the country's culture. Therefore, family consistency is needed in creating cultural attachment from early childhood, as Balinese families do in developing cultural love. This study aimed to see the Balinese tribal family in preserving Balinese culture in the Metro Rejo Oku Timur village as ancestral heritage and national identity. Get used to loving and implementing cultural values ​​in daily life, and anticipate the negative impacts of foreign cultures. This research method is a descriptive qualitative research type with the research subject being Balinese tribal families in the village of Metro Rejo Oku Timur using interview data from 15 respondents through data validity techniques using method triangulation and source triangulation. Then, the results of this study indicate that Balinese tribal families consistently provide the best education by including a series of cultural activities continuously and supported by the surrounding environment as a complement. From early childhood, Balinese children have been taught how to pray, make offerings, learn Balinese dance, compose gobagan and get used to using Balinese in their daily lives.